Cross-national research and international business: An interdisciplinary path. Issue 1 (February 2017) - Chabowski, Brian R.; Samiee, Saeed; Hult, G. Tomas M.
Highlights: Using international business, sociology, and psychology, research prospects are presented. The knowledge structure of interdisciplinary cross-national research is shown. The research levels of international, national, subnational, and individual are identified. Abstract: Comparative cross-national research is among the oldest approaches of scientific inquiry in the social sciences. We investigate the foundations of published works in cross-national research (CNR) in international business (IB), sociology, and psychology with an eye on leveraging their rich traditions for future IB research. Our approach aims to contribute and address repeated calls for taking an interdisciplinary approach in IB. We examined published CNR in 106 scholarly journals and identified 817 articles with 51, 738 citations in IB, 477 works with 30, 017 citations in sociology, and 835 articles with 54, 519 citations in psychology. We use metric multidimensional scaling to examine the co-citation data for each field and identify knowledge and approaches commonplace in sociology and psychology to propose future research paths in IB. In particular multilevel analysis, which is scarcely used in IB, offers the potential of unfolding new dimensions within the field. Based on the emergent results from our MDS solutions, we recommend multiple future paths for CNR, particularly with respect to IB relationships, market entry, and related domains.